Host immune response to A(H1N1)pdm09 vaccination and infection: A one-year prospective study on six cohorts of subjects - Liu, Wei; Ma, Mai-Juan; Tang, Fang; He, Cui; Zhang, Xiao-Ai; Jiang, Lan-Fen; Xin, Dong-Sheng; Hu, Chun-Yan; Looman, Caspar; Cao, Wu-Chun (Vaccine, 2012)
► Single dose of A(H1N1)pdm09 vaccine stimulates antibody mean lives of 8.35 months. ► Natural infections had lower antibody level and longer duration than vaccination. ► Pre-vaccination with seasonal flu vaccine led to antibody reduction to A(H1N1)pdm09 virus. ► Pre-vaccination with A(H1N1)pdm09 had no effect on seasonal influenza vaccination. The long-term immunogenicity after novel vaccine against A(H1N1)pdm09 administration or natural infection has not been well investigated. Six cohorts of subjects were followed up for over one year: one-dose A(H1N1)pdm09 vaccine recipient, A(H1N1)pdm09-seasonal trivalent vaccine recipients in different orders, confirmed A(H1N1)pdm09 patients without vaccination, with previous A(H1N1)pdm09 or seasonal influenza vaccination. Peripheral blood mononuclear cells and sera samples were collected at baseline and month 1, 2, 3, 7 and 14 after vaccination (infection). The immunogenicity was determined by hemagglutination-inhibition (HI) and B cell enzyme-linked immunospot (ELISPOT) assays. Single dose of A(H1N1)pdm09 vaccine elicited antibody titer of greater than 1:40 in 40% adults for 1 year and mean live of this adequate antibody was determined as 8.35 months. In contrast, responses after natural infections had lower peaking level and a relatively longer antibody duration, with estimated mean lives of 11.8 months. Pre-vaccination with the seasonal flu vaccine led to a significant reduction in HI titer to A(H1N1)pdm09 one month after vaccination, while pre-vaccination with A(H1N1)pdm09 had no effect on seasonal influenza vaccination. Seasonal flu vaccination followed by A(H1N1)pdm09 infection elicited boosting effect on antibody response against A(H1N1)pdm09. A similar memory B cell response was elicited from both vaccination and infection by ELISPOT assay. The long-term decay of immunity for A(H1N1)pdm09 vaccine and natural infection indicates the need of revaccination after the host lose protection acquired from either vaccination or infection. Prior infection, rather than the pre-vaccination with seasonal influenza could act on the host immunity to elicit boosting effect on the A(H1N1)pdm09.